Controllable Synthesis of Nanostructured Ca-P Coating on Magnesium Alloys via Sodium Citrate Template-Assisted Hydrothermal Method and Its Corrosion Resistance - Jieling Wei (Coatings, 2020)
In this study, a nanostructured needle-like hydroxyapatite (HA) coating was prepared by the sodium citrate template-assisted hydrothermal method on magnesium alloy (AZ31). The influence of sodium citrate on the composition, microstructure and corrosion behavior of the coatings was studied. The results showed that with the increase in the mole ratio of Ca/sodium citrate from 1 to 13, the coating gradually changed from the needle-like morphology of HA to the flake morphology of β-tricalcium phosphate (β-TCP), which was related to the existing form of citrate in the solution and the trend of complexation reaction. When the mole ratio of Ca/sodium citrate was 1, the HA coating sample with the nano needle-like morphology had a high corrosion resistance (Rt = 235.300 ± 3.584 kΩ·cm2), which was almost 200 times that of the naked AZ31 alloy. Moreover, the corrosion rates of the Ca-P coated AZ31 alloy stabilized at about 0.55 mm/year and could provide more than 56 days of corrosion protection to the samples, which approximated the degradation rate requirement for biomaterials used as bone fixture.